In Vivo Optical Molecular Imaging of Matrix Metalloproteinase Activity following Celecoxib Therapy for Colorectal Cancer - Rahul A. Sheth; Alexandra Kunin; Lars Stangenberg; Mark Sinnamon; Kenneth E. Hung; Raju Kucherlapati; Umar Mahmood (Molecular Imaging)
We present an optical molecular imaging approach to measure the efficacy of the cyclooxygenase-2 (COX-2) inhibitor celecoxib on tumor growth rate through its effect on matrix metalloproteinase (MMP) activity. A xenograft model of colorectal cancer was generated in nude mice, which were then randomized to receive celecoxib versus vehicle. MMP activity was measured by an enzyme-activatable optical molecular probe. A novel genetically engineered mouse (GEM) model of colorectal cancer was also used to assess celecoxib's effect on MMP activity, which was measured by quantitative fluorescence colonoscopy. Subcutaneously implanted xenograft tumors were 84% (SD 20.2%) smaller in volume in the treatment group versus the control group. Moreover, treated animals exhibited only a 7.6% (SEM 9%) increase in MMP activity versus 106% (SEM 8%) for untreated animals. There was an apparent linear relationship ( r = .91) between measured MMP activity and tumor growth rate. Finally, in the GEM model experiment, treated murine tumors remained relatively unchanged in volume and MMP activity; however, untreated tumors grew significantly and showed an increase in MMP activity. This method may provide for the improved identification of patients for whom COX-2 inhibition therapy is indicated by allowing one to balance the patient's cardiovascular risk with the cancer's responsiveness to celecoxib.